2015
DOI: 10.1002/hep.27922
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Simeprevir/Sofosbuvir in Hepatitis C–Infected Patients With Compensated and Decompensated Cirrhosis

Abstract: Background/Aims Risks and benefits of simeprevir plus sofosbuvir in patients with advanced cirrhosis are unknown. We assessed the safety and sustained virologic responses (SVR) of simeprevir plus sofosbuvir with and without ribavirin in patients with Child-Pugh (CP)-B/C vs. CP-A cirrhosis and compared to matched untreated controls. Methods Multicenter cohort of adults with HCV genotype 1 and cirrhosis treated with simeprevir plus sofosbuvir with/without ribavirin for 12 weeks. Controls were matched on treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
91
1
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(100 citation statements)
references
References 14 publications
6
91
1
2
Order By: Relevance
“…[33][34][35][36] Many of these trials included patients awaiting LT, 31,37 and those with decompensated cirrhosis of liver. 31,38,39 There are several controlled trials with interesting acronyms such as ALLY-1, SOLAR-1, SOLAR-2, SATURN and CORAL-1, which have shown that it is now feasible to treat patients with decompensated cirrhosis (Table 1). In addition, there have been several real world data studies which have given similar conclusions.…”
Section: Feasibility and Effectivenessmentioning
confidence: 99%
“…[33][34][35][36] Many of these trials included patients awaiting LT, 31,37 and those with decompensated cirrhosis of liver. 31,38,39 There are several controlled trials with interesting acronyms such as ALLY-1, SOLAR-1, SOLAR-2, SATURN and CORAL-1, which have shown that it is now feasible to treat patients with decompensated cirrhosis (Table 1). In addition, there have been several real world data studies which have given similar conclusions.…”
Section: Feasibility and Effectivenessmentioning
confidence: 99%
“…Ten patients died, mainly from complications related to hepatic decompensation. 27 The results of another study by Saxena and associates 28 evaluated the use sofosbuvir and simeprevir with or without ribavirin for treatment of patients with compensated and decompensated cirrhosis from HCV genotype 1. The study enrolled 160 patients, with 35% scored as Child-Pugh class B/C.…”
Section: Decompensated Cirrhosismentioning
confidence: 99%
“…Furthermore, SVR12 was achieved by 74% of patients with early severe recurrent hepatitis who did not undergo retransplant (74% with sofosbuvir and ribavirin and 71% with sofosbuvir and pegylated interferon with ribavirin). 28 Several reports have demonstrated the effectiveness of sofosbuvir and simeprevir in the posttransplant setting. The use of simeprevir is contraindicated in recipients who are receiving cyclosporine as part of the immunosuppressant regimen.…”
Section: Compensated Liver Diseasementioning
confidence: 99%
“…12 The PRO/PROD regimen is contraindicated in patients of 87%. 20 The group that received sofosbuvir/velpatasvir plus ribavirin for 12 weeks achieved the highest SVR12 rate (94%) compared to the groups without ribavirin for 12 weeks (83%) or 24 weeks (86%).…”
Section: Pre-liver Transplant Settingmentioning
confidence: 99%